Centella asiatica Alters Metabolic Pathways Associated With Alzheimer’s Disease in the 5xFAD Mouse Model of ß-Amyloid Accumulation - Speers, Alex B.; García-Jaramillo, Manuel; Feryn, Alicia; Matthews, Donald G.; Lichtenberg, Talia; Caruso, Maya; Wright, Kirsten M.; Quinn, Joseph F.; Stevens, Jan F.; Maier, Claudia S.; Soumyanath, Amala; Gray, Nora E. (Frontiers in Pharmacology, 2021)
Centella asiatica is an herb used in Ayurvedic and traditional Chinese medicine for its beneficial effects on brain health and cognition. Our group has previously shown that a water extract of Centella asiatica (CAW) elicits cognitive-enhancing effects in animal models of aging and Alzheimer’s disease, including a dose-related effect of CAW on memory in the 5xFAD mouse model of ß-amyloid accumulation. Here, we endeavor to elucidate the mechanisms underlying the effects of CAW in the brain by conducting a metabolomic analysis of cortical tissue from 5xFAD mice treated with increasing concentrations of CAW. Tissue was collected from 8-month-old male and female 5xFAD mice and their wild-type littermates treated with CAW (0, 200, 500, or 1,000 mg/kg/d) dissolved in their drinking water for 5 weeks. High-performance liquid chromatography coupled to high-resolution mass spectrometry analysis was performed and relative levels of 120 annotated metabolites were assessed in the treatment groups. Metabolomic analysis revealed sex differences in the effect of the 5xFAD genotype on metabolite levels compared to wild-type mice, and variations in the metabolomic response to CAW depending on sex, genotype, and CAW dose. In at least three of the four treated groups (5xFAD or wild-type, male or female), CAW (500 mg/kg/d) significantly altered metabolic pathways related to purine metabolism, nicotinate and nicotinamide metabolism, and glycerophospholipid metabolism. The results are in line with some of our previous findings regarding specific mechanisms of action of CAW (e.g., improving mitochondrial function, reducing oxidative stress, and increasing synaptic density). Furthermore, these findings provide new information about additional, potential mechanisms for the cognitive-enhancing effect of CAW, including upregulation of nicotinamide adenine dinucleotide in the brain and modulation of brain-derived neurotrophic factor. These metabolic pathways have been implicated in the pathophysiology of Alzheimer’s disease, highlighting the therapeutic potential of CAW in this neurodegenerative disease.